PEMBINAAN MORAL DAN KREATIVITAS REMAJA - S. Sumihatul Ummah MS; Mosleh Habibullah; Hasan Basri (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Entering teen-age, in general, either adolescent son or daugther is hard to be arranged though by its own parents. This matter is problem had by each adolescences, there are four the important matters which become fundamental study at this research, that is: (1) Condition of moral and adolescent creativity in countryside of Bancelok, (2) Effort of moral construction and adolescent creativity in countryside of Bancelok, (3) Resistances faced in moral construction and adolescent creativity in countryside of Bancelok, and also (4) Effort is done to increase the moral construction and adolescent creativity [in countryside of Bancelok. This Research uses approach qualitative. There are four elements becoming the source of informations in this research, that is; old fellow, elite figure society, government officer, and young man figure. Whereas relating to field study (data collecting) using the observation method, interview, and documentation. Later, data that is gathered to be analysed using two approaches, that is: descriptive informative and descriptive analysis.